Dekonstruksi Isu Homoseksual Konteks Sodom dan Gomora: Respons terhadap Perspektif Emanuel Gerrit Singgih - Belay, Yosep (Sekolah Tinggi Teologi Kharisma, 2025)
Abstract This article aims to analyze the reading method of homosexual issues in the context of Sodom and Gomorrah by Emanuel Gerrit Singgih and provide responses from different perspectives. The emphasis on the term